Highlights from the Third European International Society for Computational Biology (ISCB) Student Council Symposium 2014. Issue 3 (December 2015) - Francescatto, Margherita; Hermans, Susanne; Babaei, Sepideh; Vicedo, Esmeralda; Borrel, Alexandre; Meysman, Pieter
Abstract In this meeting report, we give an overview of the talks, presentations and posters presented at the third European Symposium of the International Society for Computational Biology (ISCB) Student Council. The event was organized as a satellite meeting of the 13th European Conference for Computational Biology (ECCB) and took place in Strasbourg, France on September 6th, 2014.